Structural-Semantic Features of Parenthetical Constructions (by Material of Modern English Fiction) - I. S. Shishkina; A. Yu. Mironina (Научный диалог, 2019)
The article is devoted to the study of structural models and semantic content of parenthetical structures presented in the texts of modern English fiction. The relevance of the study is due to its focus on studying parenthetical corpus of modern English language in the framework of general scientific problem “a man in a language.” The novelty of the study lies in the fact that it is made on the modern language material (texts by S. King, D. Barnes, Y. McEwan, D. Mitchell, D. Coe), not studied previously in terms of parenthetical structures functioning. Attraction of new language material presented by 736 contexts and the use of component, distributional, transformational, contextual analysis methods and method of quantitative calculations have allowed to deepen the existing knowledge about the structure and semantics of parenthetical constructions in the English language. In particular, it was found that the most typical structural models of parenthetical constructions in modern English prose are word forms, phrase and simple sentence. The most characteristic for the semantic content of the considered constructions is refinement / detailing (of a character’s image, its state or a situation), the expression of the author’s position, as well as the introduction of additional rema. The functions of concretisation and explanatory comment can be recognized as the most frequent functions of parenthetical constructions.